2018
DOI: 10.11159/icsenm18.130
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength of Reinforced Concrete Beams Made with Recycled Aggregate

Abstract: Using recycled concrete aggregate in new concrete mixes saves landfill space, reduces the need for gravel mining, and decreases pollution from transporting concrete to and from worksites. Recycled concrete aggregate may come from a variety of sources but the most common source is the demolition waste of old concrete structures. In this study, the recycled aggregate was obtained locally from Bee'ah's facility in Sharjah, UAE, and the percentage of coarse aggregate replacement in the concrete mix was either 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, research conducted on the structural behavior of RCA is limited and often contradictory. In general, flexural and shear crack patterns of 100% replacement of recycled aggregate concrete and conventional normal weight concrete are identical; nonetheless, shear capacity in recycled aggregate concrete is relatively less than that of conventional concrete [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Addition of fibers and supplementary cementitious materials was an approach to improve the mechanical properties and flexural strength of recycled aggregate mixes.…”
Section: Introductionmentioning
confidence: 99%
“…However, research conducted on the structural behavior of RCA is limited and often contradictory. In general, flexural and shear crack patterns of 100% replacement of recycled aggregate concrete and conventional normal weight concrete are identical; nonetheless, shear capacity in recycled aggregate concrete is relatively less than that of conventional concrete [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Addition of fibers and supplementary cementitious materials was an approach to improve the mechanical properties and flexural strength of recycled aggregate mixes.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, this study's overarching goal was to make design recommendations for shear and flexure, encompassing the potential integration of locally produced recycled coarse aggregate within concrete beams. This research builds on the previous work of the senior authors on the subject by greatly extending the experimental and theoretical components of the study [36,37].…”
Section: Rahal and Elsayedmentioning
confidence: 89%
“…Recently, the use of Recycled Concrete Aggregate (RCA) instead of normal Aggregate (RA) in different proportions in beams to compare the shear strength of reinforced concrete has been widely studied for a variety of reasons, including being more effective, saving material, providing more height at the central span, and being more shear resistant. As shown in research done by Tabsh and Yehia [10], Fathifaz et al [11], Pedro et al [12], and Hamoodi et al [13]. These studies have concluded that the use of RCA instead of RA in beams does not show major variations in mechanical or toughness between aggregates from controlled sources and those from precast rejects.…”
Section: Introductionmentioning
confidence: 86%